Evaluation of the Reax Force-Field for Studying the Collision of an Energetic Proton with the DNA - De Faria, Jhaison C.; Paupitz, Ricardo [UNESP]; Van Duin, Adri C. T.; Bernal, Mario A. (American Chemical Society (ACS), 2022)
The early DNA damage induced by ionizing radiation depends on how ionizing particles transfer energy to this molecule and the surrounding medium, mostly water. In preliminary studies, we found that the energy transferred by a 4 keV proton to a cytosine-guanine base pair in a classical simulation collision using the ReaxFF potential is much smaller than that obtained by a quantum calculation using time-dependent density functional theory (TDDFT). We observed that there are two main reasons for that: no accurate force-field for this situation and problems while dealing with the proton charge during the collision. Here, we only focus on the interaction potential. We calibrated the van der Waals energy term of the ReaxFF potential using TDDFT calculations and a genetic algorithm, specifically for the interaction of a proton with the DNA constituent atoms (carbon, hydrogen, phosphorus, nitrogen, and oxygen). We obtained a significant improvement in the interaction potential and, consequently, in the scattering angle of the proton colliding with the target atoms in question. However, we conclude that despite the improvement for the force-field and scattering angle, the classical charge equilibration method should also be improved to properly describe the proton-DNA collision process.